Acquired severe pneumonia in the community in seropositive HIV patients. - Héctor Cruz de los Santos; Roberto Travieso Peña; Eddy Pereira Valdes; Argelio A. Santana Cano; Rubén Bembibre Taboada (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Infection due to the Human Immunodeficiency Virus (HIV)has become a principal health problem worldwide mainly in underdeveloped countries. In these patients, respiratory infections constitute the greatest cause of morbimortality rate in which Pneumocystis Carinii is the most frequently found pathogen. However, this article describes the case of a woman who is seropositive to HIV and who developed a severe and rapidly fatal community acquired pneumonia dur to Sthaphylococcus aureus, a very rare and less common infection in this kind of patients.